Relative contribution of different members of OsDREB gene family to osmotic stress tolerance in indica and japonica ecotypes of rice. (22nd December 2021) - Chakraborty, K.; Jena, P.; Mondal, S.; Dash, G. K.; Ray, S.; Baig, M. J.; Swain, P.
ABSTRACT: Drought/osmotic stress is the single largest production constraint in rain‐fed rice cultivation. Different members of the DREB gene family are known to contribute to osmotic stress tolerance. In this study, an attempt was made to understand their relative contribution towards osmotic stress tolerance in indica and japonica ecotypes of rice. Two genotypes (one tolerant and one susceptible) from each ecotype were grown hydroponically, and 21‐day‐old seedlings were subjected to polyethylene glycol‐induced osmotic stress (15% PEG‐6000, equivalent to −3.0 bars osmotic potential). The tolerant genotypes CR143 and Moroberekan were found to have superior root traits (total root length, surface area and volume), better plant water status and increased total dry biomass as compared to their susceptible counterparts after 10 days of osmotic stress. Different members of the DREB gene family were differentially induced in response to osmotic shock (1 h after stress) and osmotic stress (24 h after stress), which also differed between the two rice ecotypes. From the gene expression profiles of 10 DREB genes (both DREB1 and DREB2 families), in indica two DREB genes, DREB1B and DREB1G, were significantly correlated with stress tolerance indices, whereas in japonica significant correlations with five DREB genes ( DREB1A, DREB1B, DREB1D, DREB1E and DREB2B ) were observed. We found that only one member, i.e . DREB1B, showed a significant correlation with drought tolerance indices in both indica and japonica ecotypes. This study provides an overview of the relative contribution of different members of the DREB gene family and their association with drought/osmotic stress tolerance in rice. Abstract : Among different members of Dehydration‐Responsive Element‐Binding ( DREB ) gene family DREB1B plays the most important role in osmotic stress tolerance in both indica and japonica ecotypes of rice.